The trans-national framework and global culture for teachable American literature in Islamic higher education institutions - Didik Murwantono; Nailil Muna (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
In recent years, innovative approaches in teaching American literature focused on the trans-national mind have been actualized in the teaching and learning proses. From this perspective, the main reason for this research is to examine the perceptions of the American mind toward Islamic students studying in the American literature class. Forty (N=40) undergraduate students contributed to this research. It was under mixed-method research by separating both quantitative and qualitative. The technique of data analysis was by simple numeric of SPSS 23 along with phenomenological exploratory analysis. The primary data were from the semi-structured online interviews and questionnaires of the students from September to November 2021. This research results that the trans-national framework has significant contributions, meanwhile global culture has a positive impact on undergraduate students in understanding American literature class. Secondly, undergraduate students in Islamic Higher Education successfully can open their perspectives to see the phenomena of the world in understanding the profound meaning of both perception and interpretation of literary works through the transnational framework. The conducted research proves that the integration of this type of transnational framework and global culture into the content of teaching American literature is not only possible but also promising. It helps to become successful lecturers for teaching American literature in the future.